ORGANIZATION OF CAREER GUIDANCE USING ROAD MAPPING TECHNOLOGY - Valentin P. Babintsev; Sergey I. Basalay; Ivan S. Bolotin; Natalya A. Silkina (Moscow Polytechnic University, 2016)
The article presents the organization of professional orientation work with students at the metallurgical enterprise. The results of the sociological survey conducted by the authors revealed the topical problems concerning career guidance. So, the demand for blue-collar jobs has decreased among high school graduates as well as an entrance competition in higher education institutions on specialties required in economy of the region. Young people prefer to choose professions with a broad scope of application and employment opportunities; employment in steel industry after graduating from vocational schools graduates consider as a residual. The article focuses on the measures for solution of the problem of job placement in the region. The implementation of the project technologies in particular road mapping for students' career guidance allowed us to obtain tangible results.